Exploiting the Achilles' heel of membrane trafficking in trypanosomes. (December 2016) - Zoltner, Martin; Horn, David; de Koning, Harry P; Field, Mark C
Highlights: Development of new drugs against trypanosomes is a crucial but unmet need. Membrane transport, endocytosis and related processes have been proposed as drug targets. Recent insights uncovered the mode of action of two drugs that are already in the clinic. Both of these drugs, suramin and pentamidine, bind surface proteins. It is possible that endocytosis is a common component of sensitivity to suramin and pentamidine. Abstract : Pathogenic protozoa are evolutionarily highly divergent from their metazoan hosts, reflected in many aspects of their biology. One particularly important parasite taxon is the trypanosomatids. Multiple transmission modes, distinct life cycles and exploitation of many host species attests to great prowess as parasites, and adaptability for efficient, chronic infection. Genome sequencing has begun uncovering how trypanosomatids are well suited to parasitism, and recent genetic screening and cell biology are revealing new aspects of how to control these organisms and prevent disease. Importantly, several lines of evidence suggest that membrane transport processes are central for the sensitivity towards several frontline drugs.